Europeanisation to the eastern borders - Tostes, Ana Paula (2022)
The geopolitical condition in Eastern Europe brings about a new dynamic of governance. The neighbourhood matters for the EU, even more so after the 2000’s enlargements. This paper analyses the Europeanisation dynamics in the Republic of Moldova as a case for a critical view of the EU’s modern external governance to the Eastern borders.